Pengaruh Perlakuan Deoperkulasi Benih dan Media Perkecambahan untuk Meningkatkan Viabilitas Benih Aren (Arenga pinnata (Wurmb.) Merr.) - Rofik, Aenur; Murniati, Endang (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2008)
The research was aimed at studying the effects of seed deoperculation treatment and germination substrate to enhance viability of sugar palm seed. This research was conducted from February until August 2006 at Seed Science and Technology Laboratory and Turfgrass area. Randomized block design with 2 factors was used in this research. The first factor consisted of five treatments namely: control, without seed treatment (P0), deoperculation with sand paper precisely on the embryo position (PI), deoperculated seed and heating in the incubator at 40oC for 5 minutes (P2), deoperculated seed and soaking in the potassium nitrate (KNO3 0.5%) for 36 hours (P3) and deoperculated seed, soaking in the potassium nitrate for 36 hours and heating in the incubator at 40oC for 5 minutes (P4). The second factor substrate used for germination consisted of five types, i.e., sand (M1), soil and compost mixed, each in equal (1:1) portions by weight (w/w) (M2), saw dust (M3), cocopeat (M4) and paddy charcoal (M5). The result showed that seed deoperculation gave very significant effect to enhance seed viability. The interaction between seed treatment and substrate significantly influenced on potential growth, germination percentage, speed of germination, the length of embryonic axis and the length of root. The highest potential growth of 96.67% was obtained from deoperculated seed and heating in the incubator at 40oC for five minutes and germinated in sand, whereas highest germination percentage of 88.33% was reached by deoperculated seed and germinated in sand. Sand (M1), cocopeat (M4) and paddy charcoal (M5) were suitable for germination substrate of sugar palm seed. Key words: Sugar palm seed, seed viability, deoperculation, cocopeat, paddy charcoal.